VERBAL VIOLENCE IN NETIZEN COMMENTS ON SOCIAL MEDIA ACCOUNTS TIKTOK @LILU_MUKERJI (LINA MUKERJI) - Mahsusi, Juni (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2023)
This study aims to determine the forms and verbal violence used in comments on the @lilu_mukerji TikTok account. This study uses a qualitative descriptive research method. The data source in this study came from netizen comments on the social media TikTok. Data collection used the technique of simak bebas libat cakap (SBLC) with the recording method. The data were analyzed using the equivalent referential method with the comparative linking technique, namely connecting and comparing verbal violence based on the form of satire (cynicism, sarcasm, irony, satire, and innuendo). The analysis results show that verbal violence in netizen comments on the @lilu_mukerji TikTok account uses language styles in the form of words, phrases, and sentences. While the types of language styles netizens use are satire, sarcasm, cynicism, irony, and satire. Then from the 120 most dominant analysis data, namely sarcasm, as many as 53 in the form of words, phrases, and sentences. Cynicism, as many as 37 in the form of phrases and sentences. Irony as much as 17 in the form of phrases and sentences. There are 13 satires in the form of phrases and sentences, while the innuendo style is not found in this study. Keyword: Verbal Violence, Social Media, Language Style